Avaliação nas aulas de língua portuguesa como parte da constituição do sujeito-aluno: efeitos de sentido - Moraes, Maike Isaquiel Bandeira (2019)
In our research, we understand that evaluation is one of the factors that constitute the subject-student. Based on this premise, the present work shows a study regarding the effects of sense produced from some forms of school evaluation used in the discipline of Portuguese Language (PL). Taking as a theoretical basis the French Discourse Analysis (DA) in articulation with the History of Language Ideas (HLI), we seek to understand how certain forms of evaluation take part in the constitution of the subject as a student and as a member of a society. From this affiliation DA / HLI, bringing the voice of authors like Pêcheux (1995), Orlandi (1997), Nunes (2008), Guimarães (2004), we seek to present concepts from these two fields of knowledge that could help us understand the evaluation as a pedagogical practice that contributes to the construction of a discourse that has, as the main voice, the subject-teacher. Through a file made of evaluation instruments used in the discipline of Portuguese Language (such as exams, assignments, tests) that bring objective and subjective questions, in other words, that require more or less of the student's reflective capacity, we cut an analytical corpus to bring issues to be re-thought about the construction of these instruments, as well as the effects produced by qualitative and quantitative evaluations put into practice today, in the classroom. Also investigating a possible sign of the silence present in some types of evaluation instruments, we seek to find, through the analysis of the questions elaborated by the subject-teacher, what, in fact, appears as a recurrence in such evaluations.